2017
DOI: 10.15225/pnn.2017.6.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Functional and Quality of Life Assessment of Patients with Spinal Pain Syndrome

Abstract: The development of civilization leads to a continuous increase in the number of diagnoses of spinal pain syndrome in patients in each age group, thus leading to the need to develop new treatment standards. Spinal pain syndromes due to the often unknown etiology cause difficult diagnosis and introduction of effective therapy. That results in difficulties in causative treatment and thus sets pain as a leading problem in the therapy. Spinal pain syndromes are a complex clinical problem that may affect the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
1
1
0
Order By: Relevance
“…This pain was of moderate or strong intensity in nature. These studies confirmed that unfortunately, pain is an inherent element of degenerative spine disease and affects the lives of both patients and their families 25 . Research by Chin et al among patients with atypical changes and low back pain confirmed a statistically significant improvement in terms of pain and level of disability after microdiscectomy.…”
Section: Discussionsupporting
confidence: 58%
“…This pain was of moderate or strong intensity in nature. These studies confirmed that unfortunately, pain is an inherent element of degenerative spine disease and affects the lives of both patients and their families 25 . Research by Chin et al among patients with atypical changes and low back pain confirmed a statistically significant improvement in terms of pain and level of disability after microdiscectomy.…”
Section: Discussionsupporting
confidence: 58%
“…Degenerative diseases of the spine and the accompanying pain have a negative impact on the quality of life. This is mainly due to the limitation of human functioning in various spheres, which in turn leads to lowering self-esteem and limiting social activity [3,4]. The studies conducted by Khavanskaya et al [5] showed that with age the pain in the spine becomes worse, which in turn reduces the quality of life by 9%.…”
Section: Introductionmentioning
confidence: 99%